Episodic memory and the medial temporal lobe: not all it seems. Evidence from the temporal variants of frontotemporal dementia. Issue 12 (29th August 2012) - Pleizier, C Machiel; van der Vlies, Annelies E; Koedam, Esther; Koene, Teddy; Barkhof, F; van der Flier, Wiesje M; Scheltens, Philip; Pijnenburg, Yolande
Abstract : Background: Disproportionate medial temporal lobe atrophy (MTA) is an early finding in Alzheimer's disease (AD). Episodic memory impairment in AD is associated with the degree of MTA. Episodic memory impairment and MTA are also found in semantic dementia (SD) and in right temporal lobe atrophy (RTLA), the temporal variants of frontotemporal dementia, but their relationship is unclear. Objective: To compare episodic memory impairment among patients with these temporal variants of frontotemporal dementia with that of patients with AD with the same degree of MTA. Methods: Episodic memory was tested with the visual association test, and semantic memory (SM) with animal fluency and the visual association naming test. MTA was measured using a visual rating scale. Each patient with SD or RTLA was matched for MTA with two patients with AD. Comparisons of episodic memory and SM were made for patients with SD versus matched patients with AD; patients with RTLA versus matched patients with AD and for SD, RTLA and all patients with AD. Results: 27 patients with SD and 11 with RTLA were matched with 54 and 22 patients with AD, respectively. Episodic memory was less impaired in patients with SD than in those with AD (8 versus 2; p<0.001) and in patients with RTLA than in those with AD (10 versus 4.5; p=0.009). Semantic memory was more affected in patients with SD than in those with AD, and the Mini Mental State Examination score was higher in patients with RTLA than in those with AD. Comparison of the three diagnostic groups showed that episodic memory was most impaired in AD, whereas SM was most impaired in SD. Conclusion: Since episodic memory impairment is more severe in AD than in SD and RTLA, despite a comparable degree of MTA, atrophy of the medial temporal lobe alone cannot account for episodic memory dysfunction.